1986
DOI: 10.1177/019459988609500506
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in High‐Risk Head and Neck Surgery: One‐Day vs. Five‐Day Therapy

Abstract: Patients who undergo major contaminated surgery of the head and neck benefit from perioperative antibiotic prophylaxis. This study was developed to determine if 5 days of antibiotic administration would be more effective than 1 day. A multi-institutional prospective randomized double-blind study was designed. Patients who were identified as requiring pedicled flap reconstruction were potential candidates for the study. Later, patients were randomly assigned to receive cefoperazone sodium for either 24 hours or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 9 publications
2
56
0
1
Order By: Relevance
“…The management and prevention of WI are real issues in perioperative care in head and neck cancer surgery. Because WI have been found to occur in up to 15% of patients despite antibiotic prophylaxis in all recent prospective studies [1,2,4,5,6,8,9,10,11,12,17,18,19,22,23,25,27,28,31,33,34], we must consider that major head and neck cancer surgery with opening of the upper aerodigestive tract is contaminated or dirty surgery [7]. Postoperative WI tend to be polymicrobial with mixed aerobic and anaerobic flora [3,9,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management and prevention of WI are real issues in perioperative care in head and neck cancer surgery. Because WI have been found to occur in up to 15% of patients despite antibiotic prophylaxis in all recent prospective studies [1,2,4,5,6,8,9,10,11,12,17,18,19,22,23,25,27,28,31,33,34], we must consider that major head and neck cancer surgery with opening of the upper aerodigestive tract is contaminated or dirty surgery [7]. Postoperative WI tend to be polymicrobial with mixed aerobic and anaerobic flora [3,9,13].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies in head and neck cancer surgery have clearly shown the efficacy of antibiotic prophylaxis [2,8,9,31]. Different clinical controlled trials have shown that shortterm antibiotic prophylaxis (24 or 48 h) is as efficient as long-term antibiotic prophylaxis [11,17,18,25,28]. Short antibiotic prophylaxis reduces the risk of drug side effects and the risk of colonization and superinfection due to resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that: (1) Antibiotic prophylaxis reduced infection rates [12][13][14]; (2) beta-lactam antibiotics are appropriate first-line agents, with clindamycin reserved for patients with beta-lactam allergies [12][13][14][15][16][17][18][19]; and (3) prolonged courses of antibiotics do not generally result in greater reduction of infection rates. [5,[20][21][22]. However, all these studies either excluded patients receiving free flaps or had only a small number of patients having free flaps.…”
mentioning
confidence: 99%
“…Several randomized, controlled, double-blinded studies comparing various lengths of antibiotic prophylaxis have failed to show a decrease in the incidence of postoperative wound infection by prolonging the length of prophylaxis [18][19][20]. This indicates that wound infections that occur despite antibiotic prophylaxis are not caused by an inadequacy or failure of prophylaxis, but by some other cause or causes.…”
Section: Infected or "Dirty"mentioning
confidence: 99%